On the problem of spirituality (Was the ancient Greek culture of the classical period spiritual?) - F.F. Serebryakov (Ученые записки Казанского университета: Серия Гуманитарные науки)
This article puts forward the thesis that the ancient Greek culture of the classical period was not spiritual, thus treating it as “the childhood of mankind, where it developed most beautifully” (K. Marx). The latter statement should be further explained. For this purpose, we defined the meanings of the concept of spirituality stemming from our more profound understanding of the concept of spirit. Our findings reveal that spirituality is the human ability, i.e., a reflection of spiritual culture in an individual overtaken by it. However, spirituality can also have a negative meaning and turn into quasi-spirituality, the essence of which was uncovered as part of our analysis. It was shown that quasi-spirituality (similarly to the lack of spirituality) manifests the disintegration of culture involved in the process during which an individual creates themselves, as well as a form of inferiority of life, its simplification. Such “spirituality” is an abstraction of life and a sublimated spirit that replaced the lack of spirituality, vulgarity that rules “below”, “eternal” and “exalted” spirit. As an airy, stilted, broken, and pretentious, it is a ghost spirit, a surrogate spirit. Viewed from this perspective, the culture of the ancient Greeks was not spiritual. The above conclusion was confirmed by appealing to the concept of soma (body) as denoting the integrity of a personality, a unity of body and spirit (on the mental level).